2018
DOI: 10.1016/j.redox.2017.10.002
|View full text |Cite
|
Sign up to set email alerts
|

The dual role of poly(ADP-ribose) polymerase-1 in modulating parthanatos and autophagy under oxidative stress in rat cochlear marginal cells of the stria vascularis

Abstract: Oxidative stress is reported to regulate several apoptotic and necrotic cell death pathways in auditory tissues. Poly(ADP-ribose) polymerase-1 (PARP-1) can be activated under oxidative stress, which is the hallmark of parthanatos. Autophagy, which serves either a pro-survival or pro-death function, can also be stimulated by oxidative stress, but the role of autophagy and its relationship with parthanatos underlying this activation in the inner ear remains unknown. In this study, we established an oxidative str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 54 publications
1
27
0
Order By: Relevance
“…Autophagy is closely related with cell death and apoptosis in eukaryotic organisms 31 . Although it is proved that PARP1 activation plays a curial role in oxidative stress-induced cell death 32 , the precise understanding of underlying mechanisms remains elusive. Here we report several new and important findings.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is closely related with cell death and apoptosis in eukaryotic organisms 31 . Although it is proved that PARP1 activation plays a curial role in oxidative stress-induced cell death 32 , the precise understanding of underlying mechanisms remains elusive. Here we report several new and important findings.…”
Section: Discussionmentioning
confidence: 99%
“…S3). The cell counting kit-8 (ccK-8) assay (dojindo Laboratories) was used to determine the cell viability and cell proliferation according to the manufacturer's instructions and as previously described (16). d-gal was used to induce senescence in the Pc12 cells, which were pre-treated with compound c (40 ”mol/l), U0126 (10 ”mol/l) or metformin (100 ”mol/l) for 24 h for further experiments.…”
Section: Methodsmentioning
confidence: 99%
“…It is worth noting that cleaved‐PARP‐1 can take part in various forms of cell death, e.g., necrosis, autophagy and parthanatos due to its multifaceted roles. Moreover, it has been reported that specific apoptosis inhibitors often function in a type‐ and stimulus‐specific manner (Chaudhuri & Nussenzweig, ; Jiang et al, ). Therefore, whether another form of cell death is involved in baicalin‐mediated alleviation of GM‐induced cochlear hair cell ototoxicity needs further detailed analysis.…”
Section: Discussionmentioning
confidence: 99%